Farmers' perceptions shape motivation for integrated pest management (IPM): an extended technology acceptance model - Christos A. Damalas; Spyridon D. Koutroubas (Crop Protection, 2026)

Current status of herbicide resistance in global cotton production: trends and perspectives - Christos A. Damalas; Spyridon D. Koutroubas (Crop Protection, 2025)

Climate change in the “vulnerable” Eastern Mediterranean and adjacent areas: A literature review of ecological impacts and threats - Epaminondas D. Christou; Thanos Dailianis; Evangelia Chatzinikolaou; Paraskevi K. Karachle; Dimitrios Damalas; Konstantinos Tsagarakis; Evangelia Strogyloudi; Georgios Karris; Soultana Zervoudaki; Antonia Giannakourou; Maria Salomidi; Sofia Reizopoulou (Marine Environmental Research, 2025)

Zeolite Enhances the Beneficial Effects of Sewage Sludge on Barley Yield, Increases Nitrogen Use, and Improves Soil Properties - Stergios Antonoglou; Spyridon D. Koutroubas; Vasileios Antoniadis; Christos A. Damalas; Sideris Fotiadis; Theodoros Markopoulos (Journal of Soil Science and Plant Nutrition, 2025)
Biosolids and zeolite have been extensively used in agriculture; however, their interactive effects need to be further clarified under field conditions. The effects of sewage sludge (SS) and zeolite on barley grain yield, nitrogen use efficiency (NUE) and soil properties were investigated in a 2-yr field study. Treatments included four rates of SS (7.8, 15.6, 23.4, 31.2 Mg ha − 1 ) and one rate of inorganic fertilizer (IF; 120 kg N ha − 1 + 26.16 kg Ρ ha − 1 ) both applied alone and in combination with zeolite, an unamended control, and a zeolite control. The applied soil amendments stimulated crop growth and N uptake. Sewage sludge, even at the lowest rate, resulted in grain yield similar to that of the IF (1669 kg ha − 1 ). Zeolite reduced SS requirements to produce grain yield at the IF level by 40% and increased maximum grain yield of barley by 23% compared to SS alone. Zeolite increased NUE when combined with low rates of SS, primarily by enhancing N uptake efficiency compared with IF, and mitigated the adverse effect of high SS application rates on soil NO 3 – -N and electrical conductivity. Adding SS at rates up to 15.6 Mg ha − 1 in combination with zeolite improved soil organic C only in the first year. Soil DTPA-extracted Cu, Mn, and Fe levels in SS treatments were lower than those detected in the IF, except for the 15.6 Mg SS ha − 1 rate that resulted in a significant increase in Fe. Zeolite inhibited the increase in DTPA-extractable Zn induced by high SS rates. Overall, zeolite enhanced the beneficial effects of SS while mitigated its negative consequences, offering both agronomic and environmental benefits.

Seed priming with salicylic acid for improving germination attributes and early growth of wheat under salinity stress - Christos A. Damalas; Spyridon D. Koutroubas (Plant Biosystems, 2025)

Corrigendum to “Herbicide resistance evolution, fitness cost, and the fear of the superweedsˮ [Plant Sci. 339 (2024) 111934] - Christos A. Damalas; Spyridon D. Koutroubas (Plant Science, 2024)

Assimilate Remobilization in Five Spring Grain Legumes Under Mediterranean Conditions - Spyridon D. Koutroubas; Christos A. Damalas; Sideris Fotiadis (International Journal of Plant Production, 2024)
A comparative evaluation of grain legumes is essential for the effective planning of legume-based agricultural systems in a given environment. The goal of this work was to contrast the growth, translocation of assimilates, and grain yield of spring-planted common vetch ( Vicia sativa L.), red pea ( Lathyrus cicera L.), lentil ( Lens culinaris Medik.), chickpea ( Cicer arietinum L.), and field pea ( Pisum sativa L.) under rainfed Mediterranean conditions. Two cultivars of each species were cultivated on a silty clay soil in northeastern Greece for 2 years (2014 and 2015) with contrasting rainfall patterns. Chickpea and field pea exhibited better early crop growth rate than any other legume. Species differences in assimilates availability prior to grain filling affected the remobilization of assimilates to seed, which increased by 45% for every kg ha −1 rise in early dry matter accumulation. Dry matter translocation efficiency varied from 9 to 51% depending on species and year. Red pea was the best option in terms of seed yield, regardless of the seasonal rainfall. Chickpea in the drier year (2015) and field pea in the wetter year (2014) produced seed yields that were comparable to that of red pea. Lentil and common vetch were generally less productive species in terms of seed yield. Species seed yield was associated with their ability to accumulate biomass either before podding ( r = 0.52, P < 0.05) or at maturity ( r = 0.51, P < 0.05), but not with harvest index or translocation of dry matter. Findings provide new knowledge regarding growth attributes and reallocation of assimilate in five legume species grown simultaneously in the same environment, which has never been studied before. In addition, results highlight that selecting species with enhanced early or final biomass potential as well as adopting cultural practices that promote biomass accumulation in the growing season appear to be effective management strategies for improving seed yield of the tested grain legumes under Mediterranean conditions.

Herbicide resistance evolution, fitness cost, and the fear of the superweeds - Christos A. Damalas; Spyridon D. Koutroubas (Plant Science, 2024)

Weed flora composition in a young olive orchard as affected by fertilizer types - Petros Platis; Christos A. Damalas; Spyridon D. Koutroubas (Phytoparasitica, 2023)
Manure is a useful source of nutrients in olive orchards, but its effect on weed growth in such an ecosystem has not been studied. A field experiment was conducted in a six-year old olive orchard (cv. Chondrelia Chalkidikis ) in northern Greece to study the effects of two forms of fertilization (inorganic fertilizer and composted cow manure) on weeds abundance and weed flora composition (species diversity and dominance). A randomized complete block design with three treatments (inorganic fertilizer, 150 kg N ha −1 plus 205 kg P 2 O 5 ha −1 plus 205 kg K 2 O; composted cow manure, 20 Mg dry weight ha −1 ; and control) replicated three times was used. Inorganic fertilizer and composted cow manure had no significant effect on the number of weed species (F = 0.288, P > 0.05), but improved olive fruit yield by 61.6% and 57.1%, respectively, compared with the non-fertilized control. Both inorganic fertilizer and composted cow manure increased the weeds dry biomass by 133.4% and 80.8%, respectively, compared with the non-fertilized control. There was a decrease in the biomass proportion (percentage of the total weed biomass) of annual species with composted cow manure (x 2 = 6.72, P < 0.05), while no significant change in the biomass ratio of grasses and broadleaf weeds was observed. Fertilization increased the growth of Chenopodium album , mainly with the addition of inorganic fertilization; and Sonchus oleraceus , slightly more with the addition of composted cow manure. Centaurea solstitialis and Daucus carota had a high proportion only in the non-fertilized control plots. Composted cow manure can be used as an alternative fertilizer in olive orchards, without enriching weed flora in terms of species number. Long-term experiments would be useful to confirm the influence of composted cow manure on weed flora of olive orchards.

Species, Cultivar and Seasonal Effects on Nodulation and Nitrogen Utilization of Spring Mediterranean Grain Legumes - Spyridon D. Koutroubas; Christos A. Damalas; Sideris Fotiadis; Theodoros Markopoulos (Journal of Soil Science and Plant Nutrition, 2023)
Information on nitrogen economy of grain legumes during seed filling is critical for their sustainable cultivation in rainfed agroecosystems, but a comparable assessment of different legumes under the same growth conditions is lacking. The purpose of this study was to examine species, cultivar and seasonal effects on nodulation and nitrogen accumulation, remobilization, and utilization. Five grain legumes [common vetch ( Vicia sativa L.), red pea ( Lathyrus cicera L.), lentil ( Lens culinaris Medik), chickpea ( Cicer arietinum L.), and field pea ( Pisum sativum L.)], each represented by two cultivars, were grown for two years in a semiarid Mediterranean environment. There were considerable environmentally induced differences among species in nodulation, with chickpea maintaining a sufficient number of nodules (16 nodules plant ‒1 ) and nodule dry weight (57 mg plant ‒1 ) even in the drier year (2015). Pre-podding nitrogen accumulation varied among species, particularly in the wetter year (2014). Nitrogen translocation from vegetative parts to seeds was correlated with pre-podding nitrogen accumulation (r = 0.99, P < 0.01 in 2014 and r = 0.98, P < 0.01 in 2015). Interspecific differences in nitrogen translocation efficiency were enlarged under drought, with red pea exhibiting the highest (84%) and lentil the lowest value (72%). Chickpea produced the highest seed nitrogen accumulation in both years and had the highest nitrogen utilization efficiency (21 kg seeds per kg N) the drier year. Nitrogen utilization efficiency was positively correlated with nitrogen harvest index and negatively with nitrogen concentration in vegetative parts at maturity. Most trait differences were less evident within species than between species. Overall, chickpea was found to outperform other legumes in semiarid Mediterranean conditions in terms of nitrogen accumulation in seeds and nitrogen utilization efficiency.

In vitro activities of omadacycline, eravacycline, cefiderocol, apramycin, and comparator antibiotics against Acinetobacter baumannii causing bloodstream infections in Greece, 2020–2021: a multicenter study - Irene Galani; Vassiliki Papoutsaki; Ilias Karaiskos; Nikolaos Moustakas; Lamprini Galani; Sofia Maraki; Viktoria Eirini Mavromanolaki; Olga Legga; Kimon Fountoulis; Evangelia D. Platsouka; Panagiota Giannopoulou; Helen Papadogeorgaki; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
Resistance of Acinetobacter baumannii to multiple clinically important antimicrobials has increased to very high rates in Greece, rendering most of them obsolete. The aim of this study was to determine the molecular epidemiology and susceptibilities of A. baumannii isolates collected from different hospitals across Greece. Single-patient A. baumannii strains isolated from blood cultures ( n = 271), from 19 hospitals, in a 6-month period (November 2020–April 2021) were subjected to minimum inhibitory concentration determination and molecular testing for carbapenemase, 16S rRNA methyltransferase and mcr gene detection and epidemiological evaluation. 98.9% of all isolates produced carbapenemase OXA-23. The vast majority (91.8%) of OXA-23 producers harbored the armA and were assigned mainly (94.3%) to sequence group G1, corresponding to IC II. Apramycin (EBL-1003) was the most active agent inhibiting 100% of the isolates at ≤16 mg/L, followed by cefiderocol which was active against at least 86% of them. Minocycline, colistin and ampicillin-sulbactam exhibited only sparse activity (S <19%), while eravacycline was 8- and 2-fold more active than minocycline and tigecycline respectively, by comparison of their MIC 50 / 90 values. OXA-23-ArmA producing A. baumannii of international clone II appears to be the prevailing epidemiological type of this organism in Greece. Cefiderocol could provide a useful alternative for difficult to treat Gram-negative infections, while apramycin (EBL-1003), the structurally unique aminoglycoside currently in clinical development, may represent a highly promising agent against multi-drug resistant A. baumanni infections, due to its high susceptibility rates and low toxicity.

Municipal Sewage Sludge Effects on Maize Yield, Nitrogen Use Efficiency, and Soil Properties - Spyridon D. Koutroubas; Vasileios Antoniadis; Christos A. Damalas; Sideris Fotiadis (Journal of Soil Science and Plant Nutrition, 2023)
Biosolids are frequently used as organic soil additives. This 2-year field study investigated the effects of sewage sludge (SWS) application on maize ( Zea mays L.) production, nitrogen accumulation, redistribution, and nitrogen use efficiency, as well as on grain element concentrations and soil properties. Treatments included three SWS rates (20, 40, and 80 Mg ha −1 year ‒1 ), mineral fertilizer (300 kg N ha −1 year ‒1 and 26 kg P ha −1 year ‒1 ), and an unamended control. Plant samples were collected at silking and maturity in both years, while soil samples were taken following maize harvest in the second year. Maize grain yield increased by 143 kg ha −1 for every Mg increase in SWS rate. Sewage sludge application resulted in maize grain yield comparable to or even greater than that of mineral fertilizer. Nitrogen uptake and translocation to grains increased quadratically with increasing SWS rates. Nitrogen use efficiency increased with moderate SWS application (up to 40 Mg ha −1 ) but decreased with heavy application (80 Mg ha −1 ) compared to fertilizer, raising the risk of nitrogen losses. Compared to fertilizer, SWS resulted in similar or lower P and Cu concentration in the grain, as well as similar or higher K, but had no effect on N, Zn, Fe, and Mn concentration. Soil pH, NO 3 -N, and exchangeable K were similar in SWS and fertilizer, but soil Olsen P improved with SWS. There were no differences among treatments in DTPA-extractable Zn, Fe, and Cu, while Mn raised with SWS. Sewage sludge could be used to increase plant N reservoir at silking, N translocation to grains, and post-silking N uptake, allowing plants to meet their N requirements throughout the growing season. Even at 20 Mg ha −1 , sewage sludge can successfully replace mineral fertilizer in maize crop.

Exogenous application of salicylic acid for regulation of sunflower growth under abiotic stress: a systematic review - Christos A. Damalas; Spyridon D. Koutroubas (Biologia, 2022)

Nitrogen dynamics during the seed-filling period in safflower under dryland Mediterranean conditions - Spyridon D. Koutroubas; Christos A. Damalas; Sideris Fotiadis (Nutrient Cycling in Agroecosystems, 2021)

Sewage Sludge Influences Nitrogen Uptake, Translocation, and Use Efficiency in Sunflower - Spyridon D. Koutroubas; Vasileios Antoniadis; Christos A. Damalas; Sideris Fotiadis (Journal of Soil Science and Plant Nutrition, 2020)

Phosphorus and potassium uptake, translocation, and utilization efficiency in chickpea under Mediterranean conditions - Sideris Fotiadis; Spyridon D. Koutroubas; Christos A. Damalas (Nutrient Cycling in Agroecosystems, 2020)

Nitrogen Utilization and Yield Determination of Spring Mediterranean Chickpea as Influenced by Planting Date and Environmental Conditions - Sideris Fotiadis; Spyridon D. Koutroubas; Christos A. Damalas (International Journal of Plant Production, 2019)

Assembling Ecological Pieces to Reconstruct the Conservation Puzzle of the Aegean Sea - Maria Sini; Stelios Katsanevakis; Nikoleta Koukourouvli; Vasilis Gerovasileiou; Thanos Dailianis; Lene Buhl-Mortensen; Dimitris Damalas; Panagiotis Dendrinos; Xenophon Dimas; Alexandros Frantzis; Vasilis Gerakaris; Sylvaine Giakoumi; et al. (Frontiers in Marine Science, 2017)

Multi-Criteria Decision Analysis as a tool to extract fishing footprints and estimate fishing pressure: application to small scale coastal fisheries and implications for management in the context of the Maritime Spatial Planning Directive - S. KAVADAS; I. MAINA; D. DAMALAS; I. DOKOS; M. PANTAZI; V. VASSILOPOULOU (Mediterranean Marine Science, 2015)
In the context of the Maritime Spatial Planning Directive and with the intention of contributing to the implementation of a future maritime spatial plan, it was decided to analyze data from the small scale coastal fisheries sector of Greece and estimate the actual extent of its activities, which is largely unknown to date. To this end we identified the most influential components affecting coastal fishing: fishing capacity, bathymetry, distance from coast, Sea Surface Chlorophyll (Chl-a) concentration, legislation, marine traffic activity, trawlers and purse seiners fishing effort and no-take zones. By means of Multi-Criteria Decision Analysis (MCDA) conducted through a stepwise procedure, the potential fishing footprint with the corresponding fishing intensity was derived. The method provides an innovative and cost-effective way to assess the impact of the, notoriously hard to assess, coastal fleet. It was further considered how the inclusion of all relevant anthropogenic activities (besides fishing) could provide the background needed to plan future marine activities in the framework of Marine Spatial Planning (MSP) and form the basis for a more realistic management approach.

Growth, grain yield and nitrogen use efficiency of Mediterranean wheat in soils amended with municipal sewage sludge - Spyridon D. Koutroubas; Vasileios Antoniadis; Sideris Fotiadis; Christos A. Damalas (Nutrient Cycling in Agroecosystems, 2014)

Advances in Fishing Power: A Study Spanning 50 Years - Dimitrios Damalas; Christos D. Maravelias; Stefanos Kavadas (Reviews in Fisheries Science & Aquaculture, 2014)

IMAS-Fish: Integrated MAnagement System to support the sustainability of Greek Fisheries resources. A multidisciplinary web-based database management system: implementation, capabilities, utilization and future prospects for fisheries stakeholde - S. KAVADAS; D. DAMALAS; S. GEORGAKARAKOS; C. MARAVELIAS; G. TSERPES; C. PAPACONSTANTINOU; G. BAZIGOS (Mediterranean Marine Science, 2013)
This article describes in detail the “IMAS-Fish” web-based tool implementation technicalities and provides examples on how can it be used for scientific and management purposes setting new standards in fishery science. “IMAS-Fish” was developed to support the assessment of marine biological resources by: (i) homogenizing all the available datasets under a relational database, (ii) facilitating quality control and data entry, (iii) offering easy access to raw data, (iv) providing processed results through a series of classical and advanced fishery statistics algorithms, and (v) visualizing the results on maps using GIS technology. Available datasets cover among others: Fishery independent experimental surveys data (locations, species, catch compositions, biological data); Commercial fishing activities (fishing gear, locations, catch compositions, discards); Market sampling data (species, biometry, maturity, ageing); Satellite derived ocean data (Sea surface temperature, Salinity, Wind speed, Chlorophyll-a concentrations, Photosynthetically active radiation); Oceanographic parameters (CTD measurements); Official national fishery statistics; Fishing fleet registry and VMS data; Fishing ports inventory; Fishing legislation archive (national and EU); Bathymetry grids. Currently, the homogenized database holds a total of more than 100,000,000 records. The web-based application is accessible through an internet browser and can serve as a valuable tool for all involved stakeholders: fisheries scientists, state officials responsible for management, fishermen cooperatives, academics, students and NGOs.

IMAS-Fish: Integrated MAnagement System to support the sustainability of Greek Fisheries resources. A multidisciplinary web-based database management system: implementation, capabilities, utilization and future prospects for fisheries stakeholde - S. KAVADAS; D. DAMALAS; S. GEORGAKARAKOS; C. MARAVELIAS; G. TSERPES; C. PAPACONSTANTINOU; G. BAZIGOS (Mediterranean Marine Science, 2013)

Slack regulation compliance in the M editerranean fisheries: a paradigm from the G reek A egean S ea demersal trawl fishery, modelling discard ogives - D. Damalas; V. Vassilopoulou (Fisheries Management and Ecology, 2013)
Annual discard ogives were estimated using generalised additive models ( GAM s) for seven demersal fish species (or taxa) and deep‐water rose shrimp, P arapenaeus longirostris (Lucas). Analysis was based on data collected on board commercial bottom trawlers in the central Aegean Sea from 1995 to 2008. Length of specimens and fishing depth (along with year) were the variables that had the most profound effect on the proportion of fish discarded. Compliance with the established minimum catch size of marine organisms ( MS ) was very low, a fact attributed to the low selectivity of currently used mesh sizes, the market demand for undersized fish, as well as the low control and enforcement effort.

Ecological mapping and data quality assessment for the needs of ecosystem-based marine spatial management: case study Greek Ionian Sea and the adjacent gulfs - Y. ISSARIS; S. KATSANEVAKIS; M. PANTAZI; V. VASSILOPOULOU; P. PANAYOTIDIS; S. KAVADAS; A. KOKKALI; M. SALOMIDI; A. FRANTZIS; A. PANOU; D. DAMALAS; D.S. KLAOUDATOS; et al. (Mediterranean Marine Science, 2012)
Mapping of ecosystem components (natural and socioeconomic) is a prerequisite for ecosystem-based marine spatial management (EB-MSM). To initiate the process of EB-MSM in the Greek Ionian Sea and the adjacent gulfs, the main relevant ecosystem components were mapped based on existing spatial information and expert judgment. The natural components mapped included habitat types and species targeted for conservation, according to national and European legislation and international agreements. Main human activities/pressures related to fisheries, aquaculture, tourism, and industry were also mapped. In order to assess the quality of data used to map ecosystem components and therefore take into consideration the inherent uncertainty, an assessment of 5 semi-quantitative data indicators based on a pedigree matrix was conducted. Through this qualitative approach we gained information related to the sources, acquisition and verification procedures, statistical properties, and temporal & geographical correlation, along with the collection process quality of the ecosystem components under study. A substantial overlapping between ecological features and human activities was identified, confirming the need for a well-planned approach to marine space management, in order to mitigate conflicts for marine resources and conserve marine ecosystems and their associated goods and services.

Multispecies fisheries management in the Mediterranean Sea: application of the Fcube methodology - C. D. MARAVELIAS; D. DAMALAS; C. ULRICH; S. KATSANEVAKIS; A. HOFF (Fisheries Management and Ecology, 2012)
The ecosystem approach (EA) advocates that advice should be given based on a holistic management of the entire marine ecosystem and all fisheries and fleets involved. Recent developments have advanced to multi‐species, multi‐fisheries advice, rather than on a single‐species/fleet/area stock basis, bridging the gap between existing single‐species approaches and the needs of the EA. The Fleet and Fisheries Forecast method (Fcube) method estimates potential levels of effort by fleet in mixed fisheries situations to achieve specific targets of fishing mortality. Data on effort, landings and socioeconomic parameters were used for coastal and trawl fisheries in the Aegean Sea. Results pointed out the strengths and weaknesses of alternative management strategies from both a biological and socioeconomic perspective. Fcube revealed the importance of effort control in the coastal fisheries that are still managed with no effort restrictions. The present findings, although preliminary, revealed that stringent cuts to effort and catch levels are required if EA management goals are to be met. The Fcube methodology, initially developed for mixed fisheries advice in northern European waters that are managed with TACs, also proved promising in providing advice to non‐TAC fisheries.

Assessment of goods and services, vulnerability, and conservation status of European seabed biotopes: a stepping stone towards ecosystem-based marine spatial management - M. SALOMIDI; S. KATSANEVAKIS; A. BORJA; U. BRAECKMAN; D. DAMALAS; I. GALPARSORO; R. MIFSUD; S. MIRTO; M. PASCUAL; C. PIPITONE; M. RABAUT; V. TODOROVA; et al. (Mediterranean Marine Science, 2012)
The goal of ecosystem-based marine spatial management is to maintain marine ecosystems in a healthy, productive and resilient condition; hence, they can sustainably provide the needed goods and services for human welfare. However, the increasing pressures upon the marine realm threaten marine ecosystems, especially seabed biotopes, and thus a well-planned approach of managing use of marine space is essential to achieve sustainability. The relative value of seabed biotopes, evaluated on the basis of goods and services, is an important starting point for the spatial management of marine areas. Herein, 56 types of European seabed biotopes and their related goods, services, sensitivity issues, and conservation status were compiled, the latter referring to management and protection tools which currently apply for these biotopes at European or international level. Fishing activities, especially by benthic trawls, and marine pollution are the main threats to European seabed biotopes. Increased seawater turbidity, dredged sediment disposal, coastal constructions, biological invasions, mining, extraction of raw materials, shipping-related activities, tourism, hydrocarbon exploration, and even some practices of scientific research, also exert substantial pressure. Although some first steps have been taken to protect the European sea beds through international agreements and European and national legislation, a finer scale of classification and assessment of marine biotopes is considered crucial in shaping sound priorities and management guidelines towards the effective conservation and sustainability of European marine resources.

Marine alien species in Greek Seas: Additions and amendments by 2010 - A. ZENETOS; S. KATSANEVAKIS; D. POURSANIDIS; F. CROCETTA; D. DAMALAS; G. APOSTOLOPOULOS; C. GRAVILI; E. VARDALA-THEODOROU; M. MALAQUIAS (Mediterranean Marine Science, 2011)
An update of the inventory of alien marine species from the coastal and offshore waters of Greece is presented. Records were compiled based on the existing scientific and grey literature, including the HCMR database of Greek alien species (ELNAIS), technical reports, scientific congresses, academic dissertations, websites, and unpublished/personal observations. 47 species were added to the inventory, including 34 invertebrates, one vertebrate (fish), three plants, eight protozoa, and one cyanobacterium. With the new records, the inventory of alien marine species of Greece now includes a total of 237 species (33 macrophytes, 131 invertebrates, 42 vertebrates, two bacteria and 29 protozoans). Among these, the presence of the gastropodHypselodoris infucata, the bivalvesDendrostrea frons and Septifer forskaliand the chondrichthyan Rhizoprionodon acutus is reported here for the first time. Based on molecular analysis, the occurrence of Bulla arabica in Greek waters is confirmed, and the suggestion that previous records of Bulla ampulla in the Mediterranean should be considered as misidentification of B. arabica is further supported. The acclimitization status of earlier records was revised in the light of new data, and thus the fishEnchelycore anatina, Seriola fasciata andTylerius spinosissimus, the red algaeHypnea cornuta and Sarconema scinaioides, the scyphomedusaCassiopea andromeda, the cephalopodSepioteuthis lessoniana, the nudibranchChromodoris annulata and the bivalvesGastrochaena cymbium andPseudochama corbieri were upgraded from casual records to established populations. The increased rate of introductions of warm water species confirms previous findings, which link the rate of introduction in the eastern Mediterranean to climate change.

Spatiotemporal distribution and habitat use of commercial demersal species in the eastern Mediterranean Sea - STELIOS KATSANEVAKIS; CHRISTOS D. MARAVELIAS; DIMITRIOS DAMALAS; ARISTOMENIS P. KARAGEORGIS; EFTHYMIA V. TSITSIKA; CHRISTOS ANAGNOSTOU; COSTAS PAPACONSTANTINOU (Fisheries Oceanography, 2009)
Generalized additive models (GAMs) were applied to investigate the influence of spatial (subarea), temporal (season) and environmental variables (substrate characteristics, depth, temperature and salinity) on the relative abundance of 27 demersal species of commercial importance in the Aegean Sea. Twelve species exhibited decreasing population density with increasing depth, whereas the abundance of the remaining species peaked at intermediate depths. Most of the species were mainly distributed on the continental shelf and upper continental slope. The dry weight percentage of sand in the sediment was included as an important predictor in the best models of all species with a lifecycle closely related to the substrate (flatfish, skates, gurnards, mullets, anglers, scorpionfish) and in most benthopelagic species (seven of 12). The weight percentage of carbonates in the sediment was also included in the best models of most species (19 of 27). Seasonal patterns in the relative abundance of species were observed, related in most cases to the seasonal differentiation of temperature and salinity gradients. During the period of water stratification (summer and autumn) the influence of temperature or salinity on fish abundance was always greater than during the period of vertical mixing (winter). The present results are discussed in the light of fostering the current perception as to factors influencing the spatiotemporal distribution of fish, which is a prerequisite for the sustainable exploitation of commercial stocks.